Futures of tropical forests (sensu lato) - Putz, F.E.; Romero, C. (Wiley, 2014)
When net deforestation declines in the tropics, attention will be drawn to the composition and structure of the retained, restored, invaded, and created forests. At that point, the seemingly inexorable trends toward increased intensities of exploitation and management will be recognized as having taken their tolls of biodiversity and other forest values. Celebrations when a country passes this ‘forest transition’ will then be tempered by realization that what has been accepted as ‘forest’ spans the gamut from short‐rotation mono‐clonal stands of genetically engineered trees to fully protected old growth natural forest. With management intensification, climate change, species introductions, landscape fragmentation, fire, and shifts in economics and governance, forests will vary along gradients of biodiversity, novelty of composition, stature, permanence, and the relative roles of natural and anthropogenic forces. Management intensity will increase with the increased availability of financial capital associated with economic globalization, scarcity of wood and other forest products, demand for biofuels, improved governance (e.g., security of property rights), improved accessibility, and technological innovations that lead to new markets for forest products. In a few places, the trend toward land‐use intensification will be counterbalanced by recognition of the many benefits of natural and semi‐natural forests, especially where forest‐fate determiners are compensated for revenues foregone from not intensifying management. Land‐use practices informed by research designed and conducted by embedded scientists will help minimize the tradeoffs between the financial profits from forest management and the benefits of retention of biodiversity and the full range of environmental services.